2011
DOI: 10.4061/2011/529828
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a G-Quadruplex from Unfolding by Replication Protein A Using Potassium and the Porphyrin TMPyP4

Abstract: Replication protein A (RPA) plays an essential role in DNA replication by binding and unfolding non-canonical single-stranded DNA (ssDNA) structures. Of the six RPA ssDNA binding domains (labeled A-F), RPA-CDE selectively binds a G-quadruplex forming sequence (5′-TAGGGGAAGGGTTGGAGTGGGTT-3′ called Gq23). In K+, Gq23 forms a mixed parallel/antiparallel conformation, and in Na+ Gq23 has a less stable (T M lowered by ∼20°C), antiparallel conformation. Gq23 is intramolecular and 1D NMR confirms a stable G-quadruple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…According to QGRS mapper [ 47 ], the G-rich sequence used in [ 22 ] is able to form a quadruplex structure. The similarity to RPA protein OB-fold supports our results of the quadruplex preferences, as RPA was shown to bind and unwind quadruplex DNA [ 58 , 59 ]. In our study, we showed greater binding of full length IFI16 protein to quadruplex DNA arising from G-rich single stranded than to double stranded DNA from the same sequence.…”
Section: Discussionsupporting
confidence: 77%
“…According to QGRS mapper [ 47 ], the G-rich sequence used in [ 22 ] is able to form a quadruplex structure. The similarity to RPA protein OB-fold supports our results of the quadruplex preferences, as RPA was shown to bind and unwind quadruplex DNA [ 58 , 59 ]. In our study, we showed greater binding of full length IFI16 protein to quadruplex DNA arising from G-rich single stranded than to double stranded DNA from the same sequence.…”
Section: Discussionsupporting
confidence: 77%
“…A second property of hRev1 that contributes to the dissolution of the G4 DNA structure is its ability to bind to ssDNA. In this way, hRev1 is acting in a manner analogous to RPA ( 45–48 ). The added effect of hRev1 binding to ssDNA on G4 disruption is manifest in the DMS footprinting results, but it is also apparent in the stopped-flow fluorescence assays where more pronounced changes in the amplitude of the signal are observed when the amount of enzyme is increased.…”
Section: Discussionmentioning
confidence: 99%
“…These were dependent on replication polarity, suggesting that secondary structure formation can alter the binding of RPA at the replication fork in vivo (43). Similarly, Prakash et al found that RPA could stabilize G-quadruplex DNA against unfolding (55), suggesting an additional, previously unknown function of RPA in binding to non-B-DNA structures in vivo.…”
Section: Discussionmentioning
confidence: 99%